Drivers of Food Choice, Barriers to Healthy Eating and a Call to Action From Adolescents to Improve Nutritional Intake Across 18 Countries. (7th June 2021) - Fleming, Catharine; De Oliveira, Juliano Diniz; Sharma, Deepika; Schmied, Virginia; La la, Girish; Koniz-Booher, Peggy; Pérez-Escamilla, Rafael; Third, Amanda
Abstract: Objectives: Across the globe, children and adolescents are at high risk of experiencing a triple burden of malnutrition. Hence there is a need to understand what adolescents themselves perceive as the drivers of and barriers to healthier food choices. We sought to understand what adolescents themselves: see as the biggest barriers and influences on their own nutritional needs and propose as a way forward for direct action to improve their dietary choices. Methods: Adolescents' experiences of food and nutrition were collected in workshops using an innovative 'distributed data gathering' methodology. Participants (N = 655 12–18 years old adolescents) completed creative participatory workshop-based qualitative activities that explore participants' actual lived experiences simultaneously across 18 countries encompassing 5 world regions. Local country UNICEF workshop facilitators were trained to run the workshops. After completion, all workshop data were digitized and uploaded to a secure online repository for qualitative (thematic analysis) and quantitative data analyses by researchers. Results: In all 18 countries, adolescents identified a range of drivers of food choices and barriers to healthy eating. Family, social media and the internet were identified as the primary drivers of adolescents' food choices, followed by television and radio, friends, branding and advertising and celebrity endorsements Adolescents reported key structural barriers for healthy eating related to financial constraints and food environments at home, school and in the community. Adolescents also identified taste as an obstacle to healthy eating. Adolescents also voiced the need to address food insecurity, easier access to unhealthy foods and limited nutritional knowledge. They proposed action plans to improve their food choices by bringing their communities together, and where adolescents are key actors in designing the solutions. Conclusions: Major dietary challenges affecting adolescents globally, include lack of access to healthy foods due to food insecurity, unchecked food industry marketing in the context of food system dominated by ultra-processed foods. Adolescent-centered solutions to unhealthy eating need to involve multilevel and multi sectoral whole-of-society efforts. Funding Sources: UNICEF.